Virtual influencers of human appearance as a form of online communication: the case of Lil Miquela and Lu do Magalu on Instagram. - Carrillo-Durán, María Victoria (2024)
Artificial intelligence and the evolution of social networks have allowed the appearance of virtual influencers with human appearance, especially on Instagram. These can be defined as computer-designed figures that show an image like humans on social networks. This article applies an exploratory-descriptive design that aims to analyze, through a qualitative study that follows the case method, the definition of what human-looking virtual influencers are and how they act on Instagram. In addition, it’s also been analyzed how these figures work when working with brands as advertising resources. The results of this study reveal the way in which these figures behave and allow brands to understand their functioning as powerful supports for business communication. In addition, we provide a first study instrument through two analysis sheets that are based on literature and observation of the phenomenon on Instagram. Both sheets are applicable to other cases.